Education and tuning of natural killer cells - Vivier, Eric; Ugolini, Sophie (Henry Stewart Talks, 2009)
Innate immunity, Natural killer cells, NK cell recognition strategies, ITIM-bearing receptors, NK cell education via MHC class I recognition, Clinical manipulation of MHC class I recognition by NK cells